PENERAPAN MODEL E-LEARNING DENGAN MOODLE DAN PENGEMBANGAN BOOKMARK UNTUK PENYUSUNAN LAPORAN DOKUMEN ILMIAH - angga pratama; Hafizh Al Kautsar Aidilof; Desuriyan Ramadhan (LPPM Universitas Al Muslim, 2022)
Today's information technology is very important during this pandemic, the internet appears as a savior for the learning process in schools that have been stopped due to concerns over the transmission of the COVID-19 virus. The use of E-Learning Applications, video conferencing, Google Meet is a substitute for the closed face-to-face communication space in learning. Based on the results of survey in SMK Negeri 2 Lhokseumawe schools, that use the E-Learning method an alternative to solving learning problems to prevent the transmission of the corona virus disease (Covid-19). Second, the preparation of scientific documents to make reports is very important and the development of financial reports with office excel. The current problem is the lack of understanding of students in providing material by using Moodle application tools, secondly, the lack of understanding of material delivery in making scientific documents in the form of automatic table of contents with bookmarks. Therefore, the importance of this training for teachers and new students in understanding the applications developed. The implementation method is the activity process begins with the provision of material starting from the introduction of web services, Moodle software installation. How to set courses, course management and user management by utilizing the Moodle application. Teachers are also taught the process of uploading materials and online quizzes. Students not only get office materials but also get a way of compiling a table of contents automatically with bookmarks. The results of this service have an impact on schools regarding problem solving in the application of E-learning, post-test questions and answers, and assignments. Furthermore, there are interesting bookmarks that are of interest to students in improving student learning in preparing financial reports and documents.